Two Dimensional Finite Difference Model with a Singularity Attenuation Factor for Structural Health Monitoring of Single Lap Joints. (24th March 2023) - Nicassio, Francesco; Vergallo, Pierandrea; Vitolo, Raffaele; Scarselli, Gennaro
Abstract : A finite difference algorithm that evaluates the health conditions of a bonded joint is presented and discussed. The mathematical formulation of the problem is developed, paying particular attention to the singularity around the corners of the joint and implementing an original discretisation method of the partial differential equations governing the propagation of the elastic waves. The equations are solved under the only hypothesis of a bidimensional field. The algorithm is sensible to defects in the bonded joint and can be used as an effective structural health monitoring tool, as proven by the experiments that show close agreement with the numerical simulations.